ЛАЗЕРЛІК СƏУЛЕЛЕНУ ЖАҒДАЙЫНДАҒЫ БИДАЙДЫҢ ҚҰРЫЛЫМДЫҚ ЕРЕКШЕЛІКТЕРІ (Experimental biology, 2015)
Work is devoted studying of influence of a laser irradiation in length of a wave of 632,8 nm, an exposition 10, 60 and 180 sec, capacity 10 мВт/см2 and diameter of radiation of light 0,1 sm2 on anatomic indicators of the Kazakhstan grade of soft wheat (Triticum aestivum L) Aksay.
Keywords: influence; anatomic indicators